REVIVING THE SCHOLARLY TRADITION: A STUDY OF THE BOOK AL-GHĀYAH WA AT-TAQRĪB BY THE ASSOCIATION OF FEMALE ISLAMIC BOARDING SCHOOL CAREGIVERS AND WOMEN PREACHERS OF LAMPUNG - Khotijah, Khotijah; Wahyudin, Wahyudin; Badaruddin, Muhammad; Dedi; Wahyudi, Dedi (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
This study examines the revitalization of the kitab kuning learning tradition through the practice of studying Al-Ghoyah wa at-Taqrib conducted by the Association of Female Islamic Boarding School Caregivers and Women Preachers (JPPPM) of Lampung. Employing a participatory ethnographic approach, data were collected through five observation sessions (90–120 minutes each), five interviews, and analysis of study-related documents. The findings show that the study sessions integrate the bandongan, sorogan, and muzakarah methods, leading to three main outcomes: (1) the strengthening of kitab kuning literacy, indicated by improved fluency in reading unvowelled texts among beginner participants who had previously struggled with nahwu–sharaf structures; (2) the formation of collective female authority through muzakarah forums that consistently address practical fiqh issues such as thaharah, family zakat, and women’s ritual practices; and (3) instructional innovation in the form of rotating instructors and simple digital documentation, which helps sustain the continuity of the study despite participants’ dual responsibilities as pesantren caregivers and preachers. The main challenges include disparities in participants’ reading abilities, limited access to supporting literature, and a culture of seniority that constrains the participation of younger members. Overall, the findings affirm that JPPPM Lampung has successfully developed an adaptive learning model that strengthens the scholarly capacity of women in pesantren and contributes to the sustainability of Islamic intellectual traditions.